'A pig is a person' or 'You can love a fox and hunt it': Innovation and tradition in the discursive representation of animals. (September 2015) - Cook, Guy
In contemporary urban society, animals have been erased in many people's lives. They are generally encountered only as meat, pets, pests or vicariously in fiction and documentaries; yet the relation of humans to other animals is a matter of pressing environmental, social, economic and philosophical concern, and across the social and natural sciences there is increased interest in human–animal interaction. This situation gives rise to many different and often irreconcilable ways of talking about animals, and current debates about human–animal interaction are frequently polarised and based on incompatible standpoints, such as those of animal rights and human exceptionalism. This article analyses two interviews which exemplify such radically opposed views: one with a spokesperson for the Vegan Society, and one with a spokesperson for the Countryside Alliance, a pro-hunting pressure group. Both are placed against the background of other interviews collected as part of an ongoing larger research project on the discursive representation of animals. Each is shown to use and promote a way of speaking about animals which is at odds with mainstream establishment discourse. It is suggested that they represent two mirror-image reactions to the erasure of animals in contemporary urban life which, despite their differences, reflect a more intimate encounter with actual animals. One actively seeks to preserve and promote a traditional discourse, the other to innovate a new non-speciesist discourse. They thus reflect, in their uses of language, contrasting possible reactions to a major social and environmental change.